Next-generation ultrafiltration membranes: A review of material design, properties, recent progress, and challenges - Kammakakam, Irshad; Lai, Zhiping (Chemosphere (Oxford), 2023)
Membrane technology utilizing ultrafiltration (UF) processes has emerged as the most widely used and cost-effective simple process in many industrial applications. The industries like textiles and petroleum refining are promptly required membrane based UF processes to alleviate the potential environmental threat caused by the generation of various wastewater. At the same time, major limitations such as material selection as well as fouling behavior challenge the overall performance of UF membranes, particularly in wastewater treatment. Therefore, a complete discussion on material design with structural property relation and separation performance of UF membranes is always exciting. This state-of-the-art review has exclusively focused on the development of UF membranes, the material design, properties, progress in separation processes, and critical challenges. So far, most of the review articles have examined the UF membrane processes through a selected track of paving typical materials and their limited applications. In contrast, in this review, we have exclusively aimed at comprehensive research from material selection and fabrication methods to all the possible applications of UF membranes, giving more attention and theoretical understanding to the complete development of high-performance UF systems. We have discussed the methodical engineering behind the development of UF membranes regardless of their materials and fabrication mechanisms. Identifying the utility of UF membrane systems in various applications, as well as their mode of separation processes, has been well discussed. Overall, the current review conveys the knowledge of the present-day significance of UF membranes together with their future prospective opportunities whilst overcoming known difficulties in many potential applications. [Display omitted] •Ultrafiltration (UF) membranes recognize high-efficiency separation technologies.•A critical discussion on material design for high-performance UF membranes is always imperative in separation processes.•The methodical engineering behind the development of UF membranes on materials and fabrication mechanisms has summarized.•90% of UF membranes are made up of polymeric materials and successfully compete in industrial applications.•Challenges and future directions for the development of high-performance UF membrane systems have been discussed.